Kuwaiti Legislation After 2020: The Path of Political Reform and Its Future Prospects" - tamam ali krigi; Adnan Abdul Amir Mahdi (Tikrit Journal For Political Science, 2025)
This study aims to analyze the role of Kuwait's legislative institution, represented by the National Assembly, in advancing political reform after 2020. It focuses on key laws enacted during this period that aim to consolidate democratic principles and enhance political participation. The paper examines Kuwait's decades-long parliamentary history, highlighting the National Assembly's pivotal role in driving political reform. It also explores the impact of these reforms on Kuwait's political and social landscapes, emphasizing their contribution to democratic development and institutional stability.